2022
DOI: 10.1002/batt.202200481
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure Engineered Silicon Alloy Anodes for Lithium‐Ion Batteries: Advances and Challenges

Abstract: Due to the high theoretical lithium storage capacity and moderate voltage platform, silicon is expected to substitute graphite and serves as the most promising anode material for lithium-ion batteries (LIBs). However, substantial volume change during cycling subjects the silicon anode to electrode pulverization and conductive network damage, extensively limiting its commercial purpose. Strategies, such as alloying, nano-crystallization, and compositing, are developed against these problems. This review introdu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 149 publications
1
14
0
Order By: Relevance
“…[8,9] In fact, it has received renewed interest as silicon and silicon-based alloys and nanocomposites are strong candidates for anode materials in lithium-ion batteries. [10] A recent review of both wet and dry milling of silicon for this application highlights the advances and challenges. [11] Such milling parameters as milling time, ball/powder ratio, and milling media size have been studied for silicon in these non-reactive systems and showed that the d 90 particle diameter of 12 μm did not change significantly from 4 to 8 hours of milling time in 20 mm grinding beads.…”
Section: Resultsmentioning
confidence: 99%
“…[8,9] In fact, it has received renewed interest as silicon and silicon-based alloys and nanocomposites are strong candidates for anode materials in lithium-ion batteries. [10] A recent review of both wet and dry milling of silicon for this application highlights the advances and challenges. [11] Such milling parameters as milling time, ball/powder ratio, and milling media size have been studied for silicon in these non-reactive systems and showed that the d 90 particle diameter of 12 μm did not change significantly from 4 to 8 hours of milling time in 20 mm grinding beads.…”
Section: Resultsmentioning
confidence: 99%
“…[ 8,9 ] Most review papers in the 3D printing fields for energy storage devices ( Table 1 ) fall into the following categories. Various 3D printing‐compatible materials for electrochemical energy applications [ 6,10–12 ] 3D printing‐enabled microstructures for energy applications [ 5,13–15 ] Main‐stream 3D printing methods to compare different electrochemical performances [ 16–19 ] Different 3D printing‐enabled solid‐state energy storage devices focusing on supercapacitors and battery components [ 7,11,20 ] 3D printing‐facilitated design and prototyping trends to process or manufacture electrodes and electrolytes [ 2,8,9,21–23 ] Methods in modeling, simulation, and data analytics regarding their role in 3D printing and the general manufacturing of energy devices [ 24–26 ] …”
Section: Introductionmentioning
confidence: 99%
“…• Various 3D printing-compatible materials for electrochemical energy applications [6,[10][11][12] • 3D printing-enabled microstructures for energy applications [5,[13][14][15] • Main-stream 3D printing methods to compare different electrochemical performances [16][17][18][19] • Different 3D printing-enabled solid-state energy storage devices focusing on supercapacitors and battery components [7,11,20] • 3D printing-facilitated design and prototyping trends to process or manufacture electrodes and electrolytes [2,8,9,[21][22][23] • Methods in modeling, simulation, and data analytics regarding their role in 3D printing and the general manufacturing of energy devices [24][25][26] However, a comprehensive summary of different 3D printing mechanisms for designing and manufacturing of energy storage applications based on each battery component (i.e., anode, cathode, and electrolyte) has been rarely reported. Therefore, unlike other literature papers in Table 1, we have focused on different 3D printing techniques for electrochemical energy applications, including the electrodes and solid-state electrolytes (SSEs), featuring the role of 3D printing in energy storage device development and their applications.…”
Section: Introductionmentioning
confidence: 99%
“…So far, extensive studies have been conducted to overcome the abovementioned problems and strive to develop practical Si anodes for commercialization. Various strategies have been proposed to address the Si swelling, including the utilization of nanostructured Si, [10][11][12][13] Si-carbon composites, [14][15][16][17] Si-based alloys, [18,19] and effective binders. [20][21][22][23][24] These materials can mitigate the volume expansion of Si by accommodating the mechanical stress during lithiation/delithiation cycles.…”
Section: Introductionmentioning
confidence: 99%